1108 PERI-PROCEDURAL COMPLICATIONS AND LONG-TERM OUTCOMES IN ATRIAL FIBRILLATION PATIENTS STRATIFIED FOR CHRONIC KIDNEY DISEASE SEVERITY UNDERGOING LEFT ATRIAL APPENDAGE OCCLUSION: RESULTS FROM AN INTERNATIONAL, MULTICENTRE REGISTRY. (15th December 2022) - Magnocavallo, Michele; Della Rocca, Domenico Giovanni; Van Niekerk, Christoffel J; Gilhofer, Thomas; Ha, Grace; D´ambrosio, Gabriele; Galvin, Jennifer; Urbanek, Lukas; Schmidt, Boris; Christoph Geller, J; Lakkireddy, Dhanunaja; Di Biase, Luigi; et al.
Abstract: Background: Atrial fibrillation (AF) and chronic kidney disease (CKD) often coexist and share an increased risk of thromboembolic events. CKD concomitantly contributes to several pathophysiological changes predisposing towards a pro-haemorrhagic state. Objective: To evaluate the impact of kidney function on peri-procedural complications and clinical outcomes in AF patients undergoing left atrial appendage occlusion (LAAO) with a Watchman device. Methods: 2124 consecutive AF patients undergoing Watchman implantation at 8 different centers were categorized into CKD stage 1+2 (n=1089), CKD stage 3 (n=796), CKD stage 4 (n=170), CKD stage 5 (n=69) based on the estimated glomerular filtration rate at baseline. The primary efficacy endpoint included a composite of cardiovascular (CV) mortality, stroke, transient ischemic attack, peripheral thromboembolism (TE), and major bleeding. Results: A non-significant higher incidence of major peri-procedural adverse events (1.7% vs. 2.3% vs. 4.1% vs. 4.3%) was observed with worsening baseline kidney function (p=0.14). The mean follow-up period was 13 ± 7 months [2226 patient-years (PY)]. In comparison to CKD stage 1+2 as a reference, the incidence of the primary endpoint was significantly higher in CKD stage 3 (log-rank p-value= 0.04), CKD stage 4 (log-rank p-value= 0.01), and CKD stage 5 (log-rank p-value= 0.001). A non-significant increase in event rates for stroke/TIA and clinically relevant bleeding was observed among the four groups. LAAO led to a TE risk reduction of 72%, 66%, 62%, and 41% in each group. The relative risk reduction in the incidence of major bleeding was 58%, 44%, 51%, and 52%, respectively. Conclusion: Patients with moderate-to-severe CKD had a higher incidence of the primary composite endpoint. The relative risk reduction in the incidence of TE and major bleeding was consistent across CKD groups, irrespective of the very different risk profiles at baseline.